THE EFFECTOF GIVING MORINGA OLEIFERA LEAF JUICE FERMENTED BY CELLULOLITIC PROBIOTICS IN DRINKING WATER ON THE PERFORMANCE OF MALE BALI DUCK - A., Adisari,; Nuriyasa, I M.; Siti, N. W. (Jurnal Peternakan Tropika, 2024)
The aim of this study was to determine the effect of Moringa Oleifera leaf juice fermented with cellulolytic probiotics from drinking water on the performance of male Bali ducks. This study was held from December 2023 - February 2024 at the Udayana University Laboratory, Faculty of Animal Husbandry Field. This study used RAL or Completely Randomized Design of 4 repetitions and 4 treatments, with a total of 16 trial units. The treatment includes giving drinking water without fermented Moringa leaf juice (P0), giving fermented Moringa leaf juice in drinking water at a level of 2.5% according to body weight (P1), giving fermented Moringa leaf juice at a level of 5% according to body weight (P2), and given fermented Moringa leaf juice at a level of 7.5% according to body weight (P3). This study showed that drinking water consumption was significantly different (P<0.05), but had no significant impact (P>0.05) on body weight gain, feed consumption, feed conversion ratio and final body weight. Then it can be concluded that if given Moringa leaf juice fermented by cellulolytic probiotic bacteria through drinking water up to a level of 7.5% there is no real impact on the performance of male Bali ducks, final body weight, feed consumption, feed conversion ratio and weight gain.